2015
DOI: 10.1111/jebm.12162
|View full text |Cite
|
Sign up to set email alerts
|

A survey on the current status of pediatric nursing human resources in Sichuan province of China

Abstract: There is a nursing shortage in tertiary-level hospitals and some grade-A specialty hospitals in Sichuan, China. The shortage is worse in pediatric inpatient wards, especially in the general hospitals and some grade-B specialty hospitals. Hospital administrations need to understand the situation and offer strategies to cope for routine nursing management as well as disaster management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…First, most of the nurses in China had junior college as their foundational education which does not comprise much scientific research knowledge and skills. Second, there is still a shortage of nursing personnel in many hospitals in China (Wan and Feng, 2015;Li et al, 2018). According to the National Development Plan for Nursing Care (2016-2020) (China, 2017), the bed-to-nurse ratio should reach 1:0.4 in a noncritical department and 1:2.5-3.0 in a critical department respectively.…”
Section: Discussionmentioning
confidence: 99%
“…First, most of the nurses in China had junior college as their foundational education which does not comprise much scientific research knowledge and skills. Second, there is still a shortage of nursing personnel in many hospitals in China (Wan and Feng, 2015;Li et al, 2018). According to the National Development Plan for Nursing Care (2016-2020) (China, 2017), the bed-to-nurse ratio should reach 1:0.4 in a noncritical department and 1:2.5-3.0 in a critical department respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Sociodemographic information and medical conditions were collected via hospital information system and face‐to‐face inquiry. Surgical risk was assessed by the attending anesthesiologist according to the China Hospital Association (CHA) surgical risk evaluation form (Appendix 1) adapted from national nosocomial infections surveillance system (NNIS) risk index [17, 18]. On the day of surgery, the anxiety status of each patient was evaluated after separation from their companion.…”
Section: Methodsmentioning
confidence: 99%
“…Medical staff in provincial hospitals face greater job demands, occupational risk, and social pressure than county hospitals, which could contribute to higher levels of anxiety and depression. A survey found that there is a general shortage of medical staff in tertiary hospitals [ 26 ]. In particular, in high-stress work environments, such as tertiary hospitals, it is crucial for healthcare companies to offer support and resources to promote the mental health and wellbeing of their staff.…”
Section: Discussionmentioning
confidence: 99%